Effect of addition of ascorbate, dithiothreitol or a caspase‐3 inhibitor to cryopreservation medium on post‐thaw survival of bovine embryos produced in vitro. Issue 9 (24th June 2022) - Carrascal‐Triana, Erly Luisana; Zolini, Adriana Moreira; de King, Antonio Ruiz; Penitente‐Filho, Jurandy Mauro; Hansen, Peter J.; Torres, Ciro Alexandre Alves; Block, Jeremy
Abstract: Experiments were conducted to investigate whether supplementation of cryopreservation medium with ascorbate, dithiothreitol (DTT) or an inhibitor of caspase‐3 (z‐DEVD‐fmk) could improve post‐thaw survival of bovine embryos produced in vitro (IVP). For all experiments, embryos were harvested on day 7 after insemination and subjected to controlled‐rate freezing in medium containing 1.5 M ethylene glycol and treatments as described below. In experiments 1–3, embryos were cryopreserved in freezing medium with ascorbate (0, 0.1, 0.3 or 0.5 mM), DTT (0, 50, 100 or 200 μM) and z‐DEVD‐fmk (0, 50, 100 or 200 μM), respectively. Post‐thaw survival was assessed at 24, 48 and 72 h. For experiments 4–5, embryos were cryopreserved in freezing medium with or without 0.1 mM ascorbate. At 24 h post‐thaw, embryo total cell number, DNA fragmentation and levels of reactive oxygen species (ROS) were evaluated. Embryos subjected to freezing and thawing in medium supplemented with 0.1 mM ascorbate had greater ( p  < .05) re‐expansion rates at 24, 48 and 72 h and hatching rate at 72 h as compared to embryos not treated with ascorbate. Post‐thaw cryosurvival was not affected by the addition of either DTT or z‐DEVD‐fmk to medium used for cryopreservation. Embryos cryopreserved in medium supplemented with 0.1 mM ascorbate had reduced ( p  < .001) levels of intracellular ROS and fewer ( p  < .001) cells with DNA fragmentation. In conclusion, post‐thaw survival of bovine IVP embryos is enhanced by supplementation of freezing medium with ascorbate.